2019
DOI: 10.1038/s41598-019-43096-8
|View full text |Cite
|
Sign up to set email alerts
|

Shade tolerance in Swarnaprabha rice is associated with higher rate of panicle emergence and positively regulated by genes of ethylene and cytokinin pathway

Abstract: This study identifies characteristics of seedling, mature plant phenotypes, changes at genetic and genomic level associated with Swarnaprabha (SP) rice grown under prolonged shade and compared with Nagina 22 (N22). Coleoptile length under low red/far-red was intermediate between that in dark and red light in a 7-days growth frame. Whereas, highest rootlet number was discriminating in seedlings grown for 28 days in hydroponics. In shade, SP and N22 both showed several tolerant mature plant phenotypes, except th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Our data suggested that only SOD activity is correlated with high yield under NL and LL conditions. A similar result was previously reported by Panigrahy et al (2019). We hypothesize that tolerant genotypes might have maintained an optimal gradation of their enzyme activity associated with CO 2 fixation under LL stress through a systematic regulation of antioxidant enzymes that possibly contributed to their final photosynthetic output.…”
Section: Principal Component Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…Our data suggested that only SOD activity is correlated with high yield under NL and LL conditions. A similar result was previously reported by Panigrahy et al (2019). We hypothesize that tolerant genotypes might have maintained an optimal gradation of their enzyme activity associated with CO 2 fixation under LL stress through a systematic regulation of antioxidant enzymes that possibly contributed to their final photosynthetic output.…”
Section: Principal Component Analysissupporting
confidence: 89%
“…Recommended agronomic practices and plant protection measures were followed. Panicle emergence rate (%) was calculated from the first day to the fifth day as described by Panigrahy et al (2019). The expression and activity of SBPase were studied on these genotypes and its overall impact on the net photosynthetic rate that ultimately influences the agronomic performance of rice under LL stress.…”
Section: Grain Yield and Related Traitsmentioning
confidence: 99%
“…In Cardamine hirsuta , a species related to Arabidopsis, shade tolerance can in part be explained by higher PHYA transcript levels and phyA protein activity 165 . In other comparisons between related species or varieties of Geranium , rice, or conifers, the differential responses to shade have been related to hormonal signaling 163,164,166 . The ecological significance of the shade-avoidance response has been demonstrated but in crops it may also produce undesirable consequences because it diverts resources from storage organs, decreases the ability of plants to defend against pathogens and makes them more vulnerable to wind damage 167 .…”
Section: Phytochrome Signaling In Other Flowering Plantsmentioning
confidence: 99%
“…Phytohormones are known to have pivotal roles in regulating stress responses in plants [41]. Under low light conditions, ethylene production and signaling was induced to increase stress tolerance in Arabidopsis and rice [42,43], but its high level of release could increase the sensitivity to stress and even lead to plant death [44]. In addition, jasmonic acid (JA) is also known as plant stress hormones in higher plants [45].…”
Section: Introductionmentioning
confidence: 99%